2016
DOI: 10.18203/2320-6012.ijrms20164574
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of arrhythmias associated with acute myocardial infarction and thrombolysis

Abstract: Background: Arrhythmias are a common occurrence in ACS. This study was undertaken to analyze the incidence, frequency and type of arrhythmias in relation to the site of infarction to aid in timely intervention to modify the outcome in MI and to study the significance of Reperfusion arrhythmias.Methods: 100 patients were evaluated. ECG and cardiac enzymes were studied. Arrhythmias complicating AMI in terms of their incidence, timing, severity, type, relation, reperfusion and results were studied.Results: Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
4
9
0
Order By: Relevance
“…Overall the number of male cases is highly significant (74%) as compared to females (26%). 6 Similar observations were made by Martin TC et al, MI incidence recorded as 85% between 35 and 75 years of age, recorded prevalence of AMI was 72% in males and 28% in females which is similar to ours where AMI was 63.3% in male subjects and 33.7% in female subjects.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Overall the number of male cases is highly significant (74%) as compared to females (26%). 6 Similar observations were made by Martin TC et al, MI incidence recorded as 85% between 35 and 75 years of age, recorded prevalence of AMI was 72% in males and 28% in females which is similar to ours where AMI was 63.3% in male subjects and 33.7% in female subjects.…”
Section: Discussionsupporting
confidence: 92%
“…In current study diabetes is recorded for 23.1% subjects as risk factor of AMI which is almost similar to Mhatre MA et al which also recorded diabetes in 23% cases. 6 Similarly diabetes was found in 19% by Svensson AM et al, study. 8 Current study found AWMI (30.7%) followed by IWMI (25.1%) were the most common affected location in MI patients.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In this study, majority of the patients had anterior wall ( anterior, antero-septal& extensive anterior) myocardial infarction (54%).This is comparable with the study of Rajhans et al, 7 where overall incidence of anterior wall was higher (56%) than inferior wall which was 44%. Similarly according to Mhatre et al 8 incidence of anterior wall myocardial infarction (58%).…”
Section: Discussionmentioning
confidence: 85%